2019
DOI: 10.1080/09593330.2019.1609097
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of suspended growth process for treatment of mixture of simulated petroleum, textile, domestic, agriculture and pharmaceutical wastewater

Abstract: The unrestricted discharge of domestic and industrial wastewaters along with agricultural runoff water into the environment as mixed-wastewater pose serious threat to freshwater 2 resources in many countries. Mixed-wastewater pollution is a common phenomenon in the developing countries as the technologies to treat the individual waste streams at source are lacking due to high operational and maintenance costs. Therefore, the need to explore the potential of suspended growth process (SGP) which is a well-establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The raw effluent was a model mixture of petroleum, textile, pharmaceutical, domestic and agricultural runoff wastewater. The composition and chemicals used in simulating the various waste streams into a single mix is detailed in previous study (Egbuikwem et al, 2019). The overall characteristics of the raw mixed wastewater is presented in Table 1.…”
Section: Composition and Characteristics Of Simulated Mixed Wastewatermentioning
confidence: 99%
See 1 more Smart Citation
“…The raw effluent was a model mixture of petroleum, textile, pharmaceutical, domestic and agricultural runoff wastewater. The composition and chemicals used in simulating the various waste streams into a single mix is detailed in previous study (Egbuikwem et al, 2019). The overall characteristics of the raw mixed wastewater is presented in Table 1.…”
Section: Composition and Characteristics Of Simulated Mixed Wastewatermentioning
confidence: 99%
“…The tap water (control) was sourced from Civil and Environmental Engineering water laboratory, University of Surrey, United Kingdom. The MWW consisted a mixture of domestic, pharmaceutical, petroleum, textile waste streams and agricultural runoff wastewaters and maintained the same characteristics as reported in previous study (Egbuikwem et al, 2019). The TWW was effluent from the lab-scale suspended growth biological process, while the TPW + NUS (which served as the upper reference control for the study) was a balanced nutrients solution prepared in the recommended ratio of 4 mL of fertilizer solution to 1 L of tap water (IKEA, 2019).…”
Section: Sources and Characteristics Of Irrigation Water Solutionsmentioning
confidence: 99%
“…Increasing the industrial flow share resulted in nitrification breakdown and which, however, was recovered after prolonged adaptation of nitrifying bacteria. Furthermore, in a recent study by [113] diversified bacteria populations, sourced from municipal wastewater treatment plant, were assessed for the potential to treat simulated mixed industrial and domestic wastewater. Findings indicate that the mechanism of long-term biomass adaptation played a crucial role in development and multiplication of competent bacteria populations and acquisition of new genetic properties capable of degrading complex organic compounds of petroleum, textile and pharmaceutical origins in the mixed wastewater up to 92.1% reduction measured as COD, while maintaining stable nitrification (about 65%) [114].…”
Section: Treatment Of Mixed Industrial Effluents and Domestic Sewage By Sgbpsmentioning
confidence: 99%
“…Naresh et al 26 achieved a 98.3% reduction in BOD of MB wastewater in 9 weeks by using a TDR media biofilm reactor. Egbuikwem et al 65 observed approximately 87% of BOD removal under the aerobic condition in 97 days from the simulated mixture of dyes wastewater in a suspended growth reactor. In another study, the textile wastewater was treated using a biological aerated filter and it was observed that 99% of BOD removal was achieved under high organic loading rate 66 .…”
Section: Biochemical Oxygen Demand (Bod)mentioning
confidence: 99%
“…Similar results were reported by another researcher, where 99.8% of the color deterioration was observed in 9 weeks on treating the MB dye simulated wastewater by fixed biofilms on TDR media 26 . Moreover, the true color of simulated mixed wastewater has almost turned invisible by the suspended growth process due to the activity of microbial communities 65 . The maximum color removal can also be achieved by integrating several techniques such as ozonation, chemical coagulation, fluidized biofilm process, and electrochemical oxidation processes and also by employing the support media (like GBs, rubber, pebbles, etc.)…”
Section: Ammonia (Nh 3 )mentioning
confidence: 99%